The Relationship between Psychological Contracts and Job Satisfaction with Turnover Intention at PT. X Contact Center Service Division - Linda Fatmawati; Fernandus Hindiarto (CV. Publikasi Indonesia, 2023)
Humans are selective resources in choosing jobs and developing careers, if they are uncomfortable and there is no development at work, HR will decide or leave work. The purpose of this study is to ascertain the relationship between psychological contracts and job satisfaction and intention to leave PT.X Contact Center Services. 72 PT.X Contact Center Services personnel served as the study's sample. The Major Hypothesis is supported by the findings of the experiment assessing the impact of psychological contracts (X1) on turnover intention. This indicates that psychological contracts and the intention to leave the company are positively and significantly related. The major hypothesis is disproved, and the minor hypothesis is accepted, according to the findings of the experiment investigating the impact of job satisfaction (X2) on turnover intention. Accordingly, the intention of employees to leave their jobs is lower the higher their level of job satisfaction.